2016
DOI: 10.1117/1.jbo.21.6.065002
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability and reproducibility of optic nerve head perfusion measurements using optical coherence tomography angiography

Abstract: of optic nerve head perfusion measurements using optical coherence tomography angiography," J. Biomed. Opt. 21(6), 065002 (2016), doi: 10.1117/1.JBO.21.6.065002. Abstract. Optical coherence tomography angiography (OCTA) has increasingly become a clinically useful technique in ophthalmic imaging. We evaluate the repeatability and reproducibility of blood perfusion in the optic nerve head (ONH) measured using optical microangiography (OMAG)-based OCTA. Ten eyes from 10 healthy volunteers are recruited and scanne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 43 publications
(65 reference statements)
2
38
0
Order By: Relevance
“…The OMAG technique allows the visualization of microcirculation and is proportional to the blood flow concentration [10]. The results of Chen and coworkers are in line with our findings, since they reported that OMAG has excellent repeatability and reproducibility in identifying and quantifying ONH perfusion in healthy eyes [7,8]. However, those studies were conducted on a very small sample (10 eyes), with all scans performed by the same operator.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The OMAG technique allows the visualization of microcirculation and is proportional to the blood flow concentration [10]. The results of Chen and coworkers are in line with our findings, since they reported that OMAG has excellent repeatability and reproducibility in identifying and quantifying ONH perfusion in healthy eyes [7,8]. However, those studies were conducted on a very small sample (10 eyes), with all scans performed by the same operator.…”
Section: Discussionsupporting
confidence: 89%
“…An optical microangiography (OMAG)-based optical coherence tomography angiography (OCTA) system has been recently introduced, and has been shown to have excellent repeatability and reproducibility in the analysis of perfusion features of the ONH in healthy eyes [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Huang and colleagues [20, 21] reported that CV values between visits were 4.3 and 2.7% for the measurement of the peripapillary flow index. Wang and colleagues [22, 23] found that the CV of intravisit and intervisit was < 3.7 and < 5.2%, the ICC was > 96% in the prelaminar, laminar cribrosa and the full ONH measurements. Table 5 summarizes the latest research of the blood flow measurements in the ONH.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than using the full thickness optic nerve head slab, Chen et al isolated the pre-laminar layer to report perfusion differences between glaucoma and normal eyes, with good repeatability and reproducibility (Chen C 2016, Chen C 2016). In addition, Chen et al introduced two new indices, termed flux and normalized flux, and demonstrated good repeatability and reproducibility.…”
Section: Review Of Clinical Studies Utilizing Octamentioning
confidence: 99%